Saints, sinners, and the God of the world the Hartford sermon notebook transcribed, 1679-1680 - Mallory, Andrew Phillips, 1966- (Numen Book Series, 2011)
Saints, Sinners, and The God of the World: The Hartford Sermon Notebook Transcribed, 1679-1680 , is a complete transcription of The Hartford Sermon Notebook, a compact, bound series of notes taken from sermons delivered by the ministers Isaac Foster, Ben Woodbridge, John Whiting, Caleb Watson, and Thomas Cheever, in Hartford, Connecticut during the years 1679 and 1680. The original notebook's authorship is unknown, but whoever took the notes did a meticulous job, and the 62 sermons contained in the notebook are nearly all complete. These sermons span a two year period of colonial Connecticut history where few extant sources exist, and represent important new primary source material for scholars of colonial New England's earliest religious history